Recent Progress in Multifunctional Stimuli-Responsive Combinational Drug Delivery Systems for the Treatment of Biofilm-Forming Bacterial Infections - Davoodbasha MubarakAli; Kandasamy Saravanakumar; Archchana Ganeshalingam; Sugavaneswaran Siva Santosh; Shanali De Silva; Jung Up Park; Chang-Min Lee; Su-Hyeon Cho; Song-Rae Kim; Namki Cho; Gobika Thiripuranathar; SeonJu Park (MDPI AG, 2024)
Drug-resistant infectious diseases pose a substantial challenge and threat to medical regimens. While adaptive laboratory evolution provides foresight for encountering such situations, it has inherent limitations. Novel drug delivery systems (DDSs) have garnered attention for overcoming these hurdles. Multi-stimuli responsive DDSs are particularly effective due to their reduced background leakage and targeted drug delivery to specific host sites for pathogen elimination. Bacterial infections create an acidic state in the microenvironment (pH: 5.0-5.5), which differs from normal physiological conditions (pH: 7.4). Infected areas are characterized by the overexpression of hyaluronidase, gelatinase, phospholipase, and other virulence factors. Consequently, several effective stimuli-responsive DDSs have been developed to target bacterial pathogens. Additionally, biofilms, structured communities of bacteria encased in a self-produced polymeric matrix, pose a significant challenge by conferring resistance to conventional antimicrobial treatments. Recent advancements in nano-drug delivery systems (nDDSs) show promise in enhancing antimicrobial efficacy by improving drug absorption and targeting within the biofilm matrix. nDDSs can deliver antimicrobials directly to the biofilm, facilitating more effective eradication of these resilient bacterial communities. Herein, this review examines challenges in DDS development, focusing on enhancing antibacterial activity and eradicating biofilms without adverse effects. Furthermore, advances in immune system modulation and photothermal therapy are discussed as future directions for the treatment of bacterial diseases.